Enhancing Elementary School Students’ Cognitive Development through Volleyball Learning Using the Simulation Method on Locomotor, Non-Locomotor, and Manipulative Movements - Krisna Mukti; Agung Wahyudi (Universitas Negeri Semarang, 2025)
Physical education in elementary schools plays an important role in developing students' cognitive aspects. Volleyball learning with the simulation method is expected to improve students' cognitive abilities through the development of basic movements. This study aims to determine the effect of volleyball learning with the simulation method on improving the cognitive skills of elementary school students in the aspects of locomotor, non-locomotor, and manipulative movements. The research used an experimental method with a pre-test post-test control group design. The subjects of the study were 32 students (14 boys and 18 girls) from grade 5 of SDN 1 Saban, Gubug District. The instrument used was a validated cognitive test of basic movements. The data were analyzed using paired t-test and independent t-test. The results of the study showed a significant improvement in the cognitive abilities of students in the experimental group, with a significance value of 0.000 < 0.05. The highest improvement occurred in the manipulative movement aspect (32.5%), followed by locomotor movement (28.7%), and non-locomotor movement (25.3%). Volleyball learning using the simulation method is effective in improving the cognitive abilities of elementary school students in all aspects of basic movement studied.